Production of Lemongrass (Cymbopogon Citratus) Powder - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Lemongrass (Cymbopogon citratus) is a perennial grass belonging to genus Cymbopogon. The lemongrass has a very wide demand in nutritional, medicinal and flavoring industry. Cymbopogon citratus contains various phytoconstituents such as flavonoids and phenolic compounds, terpenoids and essential oils, which may be responsible for the different biological activities. The demand for lemongrass (Cymbopogon citratus) is for its high citral content. But it is not stored as fresh for long time at ambient condition because it turns brown and rotten quickly. Even processing or preservation, its volatility and susceptibility to degradation are the major drawbacks for the use of Cymbopogon citratus oil. This research studied the feasibility of lemongrass dried powder production by treatment of vapor steaming (140oC in 10s; 130oC in 15s, 120oC in 20s, 110oC in 25s), drying temperature (40oC, 45oC, 50oC, 55oC) in 6 hours to 6.5% moisture content, grinding and coating materials (β-cyclodextrin, sodium alginate, carrageenan, cacboxymethyl cellulose) in different concentration (1.0%, 1.5%, 2.0%, 2.5%). The total chlorophyll content (mg/100g), citral content (%) were estimated. Results revealed that vapor steaming at 130oC in 15s, drying at 50oC in 6 hours to 6.5% moisture content, grinding and coating with 2.0% of β-cyclodextrin were appropriated for lemongrass dried powder production.Keywords: Lemongrass, Dried powder, Chlorophyll, Citral, β‐cyclodextrin, Sodium alginate, Carrageenan, Cacboxymethyl cellulose